Tanggungjawab Pemerintah Dalam Pengelolaan Lingkungan Hidup Berbasis Partisipasi Masyarakat untuk Pembangunan Daerah Bali - I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Fakultas Hukum, Universitas Warmadewa, 2020)
A good and healthy environment is a human right for every Indonesian citizen as mandated in Article 28H of the 1945 Constitution of Indonesia. Unwise management of the environment contributes to the deterioration in the quality of the environment because it is necessary to increase environmental protection and management. Environmental protection and sustainable management is the responsibility of the government and the community. The responsibility of the government in carrying out environmental protection and management is a function of public services, to ensure that all residents have a good and healthy environment. Then the government can be held accountable, whether administratively, civil or criminal, when the government fails to carry out its obligations that are not in accordance with the aspirations of the community. This study is qualified as a normative legal research by applying several types of approaches, namely, the legislative approach, conceptual approach, philosophical approach, historical approach, comparative approach, case approach including cultural approaches based on the wisdom of the local community.The results showed that the protection and management of the environment is an effort to assume responsibility is very difficult so that it results in a decrease in the quality of the environment is increasingly apparent. Likewise in the event of environmental pollution and damage, the perpetrators can be held responsible both in civil law and criminal law. However, participatory environmental enforcement by integrating values that develop in the community in protecting and preserving the environment is an ideal form of protecting and prudent environmental management to realize sustainable regional development.